Pandemi Covid-19 dalam Penyajian Pelaporan Keuangan dan Keberlangsungan Usaha melalui Prediksi Kebangkrutan - Shinta Budi Astuti; Ameilia Damayanti; Tryas Chasbiandani; Nelyumna Rizal (AFRE (Accounting and Financial Review), 2020)
The main purpose of this study is to assess and analyze the business continuity (going concern) of companies before and during the Covid-19 pandemic. The sample of this research is 45 property sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2019-2020 and meet predetermined criteria. This study uses the Altman Z-Score bankruptcy prediction model to assess the business continuity of the sample companies. This research proves that there is indeed an influence from the global Covid-19 pandemic. Companies that are experiencing financial problems and have a strong potential for bankruptcy increased from 2% at the end of 2019 to 51% at the end of June 2020. DOI: https://doi.org/10.26905/afr.v3i2.5451